Involvement of the cerebellum in the regulation of executive functions in children—Preliminary analysis based on a neuropsychological study of children after cerebellar tumour surgery - Starowicz-Filip, Anna; Bętkowska-Korpała, Barbara; Yablonska, Tetiana; Kwiatkowski, Stanisław; Milczarek, Olga; Klasa, Łukasz; Chrobak, Adrian Andrzej (Frontiers in Psychology, 2022)
Aim Preliminary assessment of executive functions in children with cerebellar lesions, description of their emotional-social functioning and selection of sensitive neuropsychological tools to detect the cerebellar cognitive affective syndrome (CCAS). Materials and methods The study group consisted of 10 children after cerebellar tumour surgery. The control group consisted of 10 healthy children, matched for age and sex: The IDS-2 executive functions battery, the Conners 3 ADHD questionnaire, the Autism Spectrum Rating Scales (ASRS) and the International Cooperative Ataxia Rating Scale (ICARS) were used. Results Statistical analysis showed statistically significant differences between the experimental and control groups in terms of two dimensions of executive functioning. Children from experimental group was characterised by worse planning and divided attention than healthy controls. Moreover children with cerebellar lesions were characterised by significantly higher levels of some behaviours similar to that observed in autism spectrum disorders, namely difficulties in social relationships, self-regulation of emotions, attention, and greater behavioural rigidity. Test power analysis and estimation of the effect size by the Cohen’s d coefficient indicated that with a slight increase in the size of the experimental group, the probability of detecting statistically significant difference in the executive functions total measure score as well as in several ASRS subscales increased, but not in Conners 3 subscales. Conclusions Cerebellar damage may pose a risk for dysexecutive syndrome and social-emotional problems in children. The IDS-2 executive functions battery and the ASRS test are sufficiently sensitive tools to assess elements of the CCAS in children.